A cemented carbide insert and a method of manufacturing and using the same
Patent Information
- Application Number
- CN202611464282.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]此外,常规晶粒长大抑制剂(如VC、Cr3C2等)虽能抑制晶粒长大,但对合金的高温红硬性改善有限
本发明通过在基体配方中引入硫脲和稀土氧化物,通过预反应热处理使硫脲分解产生活性氮原子和硫原子,活性氮原子参与碳氮化物固溶体的形成,显著提升硬质合金的高温红硬性和抗断裂能力;活性硫原子则被稀土氧化物原位固定为稳定的稀土硫氧化物,一方面能够避免传统硬质合金中因硫元素富集晶界引起的“硫脆”现象,从而在保持高硬度的同时显著改善了合金的韧性和抗冲击性能;另一方面,该稀土硫氧化物在切削高温下可迁移至刀具表面形成自润滑膜,有效降低平均摩擦系数。
Smart Images

Figure CN122979729A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of cemented carbide technology, and in particular to a cemented carbide cutting tool, its preparation method and application. Background Technology
[0002] Cemented carbide, with its high hardness, high wear resistance, and good toughness, is widely used in cutting tools, mining tools, and wear-resistant parts. With the rapid development of high-end manufacturing industries such as aerospace and energy, the machining of heat-resistant alloys such as nickel-based superalloys and titanium alloys places increasingly higher demands on tool performance—tools need to maintain high hardness and wear resistance under high-temperature conditions, without significant softening, and maintain good fracture resistance under interrupted cutting conditions.
[0003] To meet these requirements, ultrafine-grained WC-Co cemented carbide has become an important development direction. However, the significant increase in the number of grain boundaries due to grain refinement has made the problem of impurity enrichment at grain boundaries increasingly prominent. Among them, sulfur, as one of the common impurity elements in cemented carbide, may reduce interfacial bonding strength due to its segregation at grain boundaries, thus affecting the toughness and impact resistance of the alloy to a certain extent. Existing technologies mainly adopt a combination of raw material purification and the addition of purifying agents to control sulfur, in order to reduce the harmful properties of sulfur.
[0004] In addition, conventional grain growth inhibitors (such as VC, Cr3C2, etc.) can inhibit grain growth, but have limited effect on improving the high-temperature red hardness of alloys. Summary of the Invention
[0005] The present invention is made in view of the above-mentioned problems, and its purpose is to provide a cemented carbide cutting tool, its preparation method and application. The cemented carbide cutting tool provided by the present invention has good fracture resistance and maintains high hardness and wear resistance under high temperature heating conditions without significant softening.
[0006] Specifically, the first aspect of the present invention provides a cemented carbide cutting tool, comprising a substrate and a coating disposed on the substrate, wherein the substrate comprises the following raw materials in weight percentages: WC: 81.5%–86.5%, Co: 10%–12%, VC: 0.75%–1.5%, TiC: 0.75%–1.5%, thiourea: 2%–4%, rare earth oxides: 0.02%–0.08%, and carbon black: 0.05%–0.15%; The rare earth oxide is Y2O3 or La2O3.
[0007] Optionally, the coating includes a transition layer and a functional layer sequentially disposed on the substrate.
[0008] Optionally, the transition layer in the coating is Cr.
[0009] Optionally, the thickness of the transition layer in the coating is 0.1 μm to 0.3 μm.
[0010] Optionally, the functional layer in the coating is at least one of TiAlN coating, AlTiN coating, TiSiN coating, TiAlVN coating, and TiAlSiN coating.
[0011] Optionally, the thickness of the functional layer in the coating is 2 μm to 5 μm.
[0012] A second aspect of the present invention provides a method for preparing a cemented carbide cutting tool, comprising the following steps: S1: After mixing the raw materials for preparing the matrix, the mixture is subjected to a first ball milling and a pre-reaction heat treatment under a protective atmosphere to obtain a mixed powder; a binder is added to the mixed powder and the mixture is subjected to a second ball milling, and then molded into a green body; the green body is then subjected to spark plasma sintering to obtain the matrix. S2: A coating is prepared on the substrate obtained in step S1 using physical vapor deposition.
[0013] Optionally, the rotational speed of the first ball mill in step S1 is 300 r / min to 350 r / min.
[0014] Optionally, the first ball milling time in step S1 is 24h to 48h.
[0015] Optionally, the rotational speed of the second ball mill in step S1 is 80 r / min to 150 r / min.
[0016] Optionally, the second ball milling time in step S1 is 1 hour to 2 hours.
[0017] Optionally, the flow rate of the protective atmosphere in the pre-reaction heat treatment in step S1 is 100 ml / min to 200 ml / min.
[0018] Optionally, the heating rate of the pre-reaction heat treatment in step S1 is 5℃ / min to 10℃ / min.
[0019] Optionally, the temperature of the pre-reaction heat treatment in step S1 is 550℃~700℃.
[0020] Optionally, the heat treatment time for the pre-reaction heat treatment in step S1 is 2h to 4h.
[0021] Optionally, the compression molding pressure in step S1 is 200MPa to 250MPa.
[0022] Optionally, the vacuum degree of the discharge plasma sintering in step S1 is 5 Pa to 15 Pa.
[0023] Optionally, the heating rate of the discharge plasma sintering in step S1 is 150℃ / min to 250℃ / min.
[0024] Optionally, the discharge plasma sintering in step S1 is divided into a first-stage sintering and a second-stage sintering.
[0025] Optionally, the sintering temperature in the first stage of step S1 is 1100℃~1200℃.
[0026] Optionally, the holding time for the first stage of sintering in step S1 is 5 min to 10 min.
[0027] Optionally, the sintering pressure in the first stage of step S1 is 10MPa to 20MPa.
[0028] Optionally, the sintering temperature in the second stage of step S1 is 1340℃~1450℃.
[0029] Optionally, the holding time for the second stage sintering in step S1 is 5 min to 15 min.
[0030] Optionally, the sintering pressure in the second stage of step S1 is 30MPa to 60MPa.
[0031] Optionally, the temperature of physical vapor deposition in step S2 is 400℃~500℃.
[0032] A third aspect of the invention provides a cutting tool for milling heat-resistant alloys, comprising one or more of the aforementioned carbide inserts.
[0033] Compared with the prior art, the present invention has the following beneficial effects: This invention introduces thiourea and rare earth oxides into the matrix formulation. Through pre-reaction heat treatment, thiourea decomposes to generate active nitrogen atoms and sulfur atoms. The active nitrogen atoms participate in the formation of carbonitride solid solutions, significantly improving the high-temperature red hardness and fracture resistance of cemented carbide. The active sulfur atoms are fixed in situ by the rare earth oxides into stable rare earth sulfur oxides. On the one hand, this avoids the "sulfur embrittlement" phenomenon caused by sulfur enrichment at grain boundaries in traditional cemented carbides, thus significantly improving the toughness and impact resistance of the alloy while maintaining high hardness. On the other hand, the rare earth sulfur oxides can migrate to the tool surface at high cutting temperatures to form a self-lubricating film, effectively reducing the average coefficient of friction.
[0034] This invention employs spark plasma sintering technology, which utilizes its rapid heating and short holding time characteristics to effectively suppress the abnormal growth of ultrafine WC grains during the sintering process, while preserving the favorable distribution of rare earth elements in the matrix, thus giving the matrix both fine grain strengthening and rare earth strengthening effects.
[0035] The carbide inserts provided by this invention have good fracture resistance in the milling of heat-resistant alloys, and can maintain high hardness and wear resistance under high temperature conditions without significant softening. Attached Figure Description
[0036] To more clearly illustrate the technical solutions in the embodiments of this drawing or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this drawing. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0037] Figure 1 This is a SEM image of the cemented carbide cutting tool substrate prepared in Example 1. Detailed Implementation
[0038] To make the objectives, technical solutions, and advantages of this application clearer, the following description and illustration are provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application. All other embodiments obtained by those skilled in the art based on the embodiments provided in this application without inventive effort are within the scope of protection of this application.
[0039] Obviously, the following description is merely some examples or embodiments of this application. Those skilled in the art can apply this application to other similar scenarios without any inventive effort. Furthermore, it is understood that although the effort involved in such development may be complex and lengthy, for those skilled in the art related to the content disclosed in this application, any changes to design, manufacturing, or production based on the technical content disclosed in this application are merely conventional technical means and should not be construed as insufficient disclosure of the content of this application.
[0040] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0041] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0042] On one hand, this application provides a cemented carbide cutting tool, comprising a substrate and a coating disposed on the substrate, wherein the substrate comprises the following raw materials by weight percentage: WC: 81.5%–86.5%, Co: 10%–12%, VC: 0.75%–1.5%, TiC: 0.75%–1.5%, thiourea: 2%–4%, rare earth oxides: 0.02%–0.08%, and carbon black: 0.05%–0.15%; wherein the rare earth oxides are Y2O3 or La2O3.
[0043] Rare earth oxides: During sintering, rare earth oxides Y₂O₃ or La₂O₃ react with active sulfur atoms produced by the decomposition of thiourea to generate stable rare earth sulfur oxides or rare earth sulfides. These compounds are distributed in the form of fine particles at the grain boundaries, transforming sulfur from a "free segregated state" to a "chemically bound state." This helps to suppress the enrichment of sulfur at the grain boundaries and its weakening of the interfacial bonding strength, thereby reducing or avoiding the harmful effects of "sulfur embrittlement" on the alloy's toughness.
[0044] Thiourea: During heat treatment, thiourea decomposes to produce active nitrogen atoms. In subsequent sintering, these nitrogen atoms have a chemical affinity for diffusing into the TiC and VC lattices and occupying interstitial sites, which is conducive to the formation of nitrogen-containing composite carbonitride solid solutions. The interstitial solid solution of nitrogen atoms causes lattice distortion, increases the resistance to dislocation movement, and strengthens the hard phase itself. At the same time, carbonitrides have high thermal stability, which is beneficial for maintaining the high-temperature hardness of the alloy.
[0045] Carbon black: When nitrogen atoms enter the carbide lattice, due to the difference in valence electron structure between nitrogen and carbon, they replace some carbon sites and release free carbon, which may cause deviations in the carbon content of the Co phase. The addition of carbon black helps to maintain the stability of the carbon content in the Co phase and reduces the risk of the formation of harmful phases (such as the η phase) due to carbon deficiency.
[0046] VC: During sintering, VC inhibits the growth of WC grains, which is beneficial to maintaining the ultrafine grain structure; at the same time, V in VC can interdiffuse with TiC, providing a vanadium source for the subsequent formation of carbonitride solid solutions.
[0047] TiC: TiC provides the titanium source needed to combine with nitrogen from thiourea decomposition to form carbonitride solid solutions.
[0048] In some embodiments of this application, the coating includes a transition layer and a functional layer sequentially disposed on the substrate.
[0049] The transition layer acts as a "stress buffer" between the substrate and the functional layer. The difference in thermal expansion coefficients and lattice constants between the substrate and the functional layer means that direct deposition of the functional layer would generate significant internal stress at the interface. The introduction of the transition layer moderates the thermal expansion gradient across the interface, reducing stress concentration at the interface caused by thermal mismatch and improving the interfacial compatibility of the coating system from a structural design perspective.
[0050] In some embodiments of this application, the transition layer in the coating is Cr.
[0051] Cr exhibits good chemical affinity with WC and Co in the matrix, as well as nitrides in the functional layer. During deposition, the Cr layer can both form a metallurgical bond with the matrix through interfacial diffusion and prevent excessive diffusion of functional layer metal elements into the matrix.
[0052] In some embodiments of this application, the thickness of the transition layer in the coating is 0.1 μm to 0.3 μm.
[0053] In this application, the thickness of the transition layer is controlled between 0.1 μm and 0.3 μm: when the thickness reaches more than 0.1 μm, a continuous, pinhole-free, dense thin layer can be formed, which is beneficial to the diffusion barrier effect of metal elements in the functional layer; when the thickness does not exceed 0.3 μm, the internal stress of the Cr layer itself is at a controllable level, which is beneficial to controlling the interface stress of the Cr layer itself.
[0054] In some embodiments of this application, the functional layer in the coating is at least one of TiAlN coating, AlTiN coating, TiSiN coating, TiAlVN coating, and TiAlSiN coating.
[0055] At high temperatures (>800℃), TiAlN coatings form a dense Al2O3 protective film on the surface, preventing oxygen from diffusing into the coating. The addition of Si in TiSiN creates a composite structure where amorphous Si3N4 encapsulates nanocrystalline TiN, enhancing hardness and thermal stability through the nanocomposite effect. The introduction of V in TiAlVN can form V2O5 during cutting, providing lubrication.
[0056] In some embodiments of this application, the thickness of the functional layer in the coating is 2 μm to 5 μm.
[0057] The thickness of the functional layer is controlled between 2μm and 5μm to ensure sufficient wear resistance life while avoiding the accumulation of internal stress and increased tendency to peel off due to excessive coating thickness.
[0058] On the other hand, this application provides a method for preparing a cemented carbide cutting tool, comprising the following steps: S1: After mixing the raw materials for preparing the matrix, the mixture is subjected to a first ball milling and a pre-reaction heat treatment under a protective atmosphere to obtain a mixed powder; a binder is added to the mixed powder and the mixture is subjected to a second ball milling, and then molded into a green body; the green body is then subjected to spark plasma sintering to obtain the matrix. S2: A coating is prepared on the substrate obtained in step S1 using physical vapor deposition.
[0059] This application places the pre-reaction heat treatment before spark plasma sintering. This allows the gases generated by thiourea to escape under pressureless conditions, reducing the number of preform defects caused by the inability to expel generated gases during subsequent spark plasma sintering. Rapid densification achieved through spark plasma sintering helps suppress abnormal growth of WC grains during sintering. Furthermore, by completing the substrate sintering and coating deposition in steps, the coating material avoids undergoing the high-temperature process of substrate sintering, thus maintaining the controllability of the coating composition and structure.
[0060] In some embodiments of this application, the rotational speed of the first ball mill in step S1 is 300 r / min to 350 r / min.
[0061] In some embodiments of this application, the first ball milling time in step S1 is 24h to 48h.
[0062] In this application, the rotation speed of the first ball mill is controlled at 300 r / min to 350 r / min, and the time is 24 h to 48 h. This is beneficial to the full crushing and mixing of the raw material particles, so that the Co powder is evenly dispersed between the WC particles, which creates the preconditions for the uniform distribution of the binder phase in the subsequent sintering process.
[0063] In some embodiments of this application, the flow rate of the protective atmosphere in the pre-reaction heat treatment of step S1 is 100 ml / min to 200 ml / min.
[0064] In this application, the flow rate of the protective atmosphere during the pre-reaction heat treatment is controlled to be 100 ml / min to 200 ml / min. The protective atmosphere is preferably nitrogen. The continuously flowing nitrogen will promptly carry away the byproducts (such as H2S, CS2, etc.) generated by the decomposition of thiourea from the reaction area, preventing the byproducts from being adsorbed again on the powder surface or competing with active nitrogen for reaction sites.
[0065] In some embodiments of this application, the heating rate of the pre-reaction heat treatment in step S1 is 5°C / min to 10°C / min.
[0066] In this application, the heating rate of the pre-reaction heat treatment is controlled at 5℃ / min to 10℃ / min, which is beneficial to control the slow decomposition and gas production of thiourea.
[0067] In some embodiments of this application, the temperature of the pre-reaction heat treatment in step S1 is 550°C to 700°C.
[0068] In this application, the temperature of the pre-reaction heat treatment is controlled at 550℃~700℃, which matches the decomposition temperature range of thiourea. At this temperature, thiourea undergoes thermal decomposition to produce active nitrogen atoms. At the same time, the nitrogen atmosphere maintains the nitrogen partial pressure in the furnace, which is beneficial to maintain the enrichment state of the decomposed active nitrogen on the particle surface.
[0069] In some embodiments of this application, the heat treatment time for the pre-reaction heat treatment in step S1 is 2h to 4h.
[0070] In this application, the holding time of the pre-reaction heat treatment is controlled to be 2h to 4h, which provides kinetic conditions for the diffusion of active nitrogen atoms to the surface and near-surface layer of carbide particles, so that the reaction precursor for the subsequent SPS sintering to form carbonitrides can be formed in advance.
[0071] In some embodiments of this application, the rotational speed of the second ball mill in step S1 is 80 r / min to 150 r / min.
[0072] In some embodiments of this application, the second ball milling time in step S1 is 1h to 2h.
[0073] In this application, the rotation speed of the second ball mill is controlled to be 80 r / min to 150 r / min, and the time is 1 h to 2 h, so that the binder is uniformly coated on the surface of the particles.
[0074] In some embodiments of this application, the molding pressure in step S1 is 200MPa to 250MPa.
[0075] In this application, the pressure of compression molding is controlled at 200MPa to 250MPa to increase the density of the green body.
[0076] In some embodiments of this application, the vacuum degree of the discharge plasma sintering in step S1 is 5 Pa to 15 Pa.
[0077] In some embodiments of this application, the heating rate of the discharge plasma sintering in step S1 is 150°C / min to 250°C / min.
[0078] In some embodiments of this application, the discharge plasma sintering in step S1 is divided into a first-stage sintering and a second-stage sintering.
[0079] During the first stage of heat preservation, particle surface diffusion dominates, achieving initial necking and pore closure. In the second stage, the temperature is increased to the final temperature, where grain boundary diffusion and volume diffusion are further completed at higher temperatures, driving the densification process. The two-stage design partially separates the densification process from the solid-phase reaction within the temperature range.
[0080] In some embodiments of this application, the sintering temperature in the first stage of step S1 is 1100℃~1200℃.
[0081] In some embodiments of this application, the holding time for the first stage sintering in step S1 is 5 min to 10 min.
[0082] In this application, the temperature of the first stage sintering is controlled at 1100℃~1200℃ and the holding time is 5min~10min. The reaction kinetic rate of rare earth oxides and sulfur is significantly improved, which is conducive to the occurrence of sulfur fixation reaction at a lower temperature. At the same time, the nucleation of carbonitrides begins to occur, which decomposes the reaction burden during subsequent high-temperature sintering.
[0083] In some embodiments of this application, the sintering temperature in the second stage of step S1 is 1340℃~1450℃.
[0084] In some embodiments of this application, the holding time for the second stage sintering in step S1 is 5 min to 15 min.
[0085] In this application, the temperature of the second-stage sintering is controlled at 1340℃~1450℃, and the holding time is 5min~15min. Co has fully melted and formed a liquid phase in this temperature range, and WC achieves particle rearrangement and densification through the dissolution and desorption mechanism. At the same time, the carbonitrides that have been nucleated before this temperature further grow and tend to stabilize through solid-phase diffusion.
[0086] In some embodiments of this application, the pressure of the first stage sintering in step S1 is 10MPa to 20MPa.
[0087] In some embodiments of this application, the pressure of the second stage sintering in step S1 is 30MPa to 60MPa.
[0088] The switching between the first stage of low pressure (10MPa~20MPa) and the second stage of high pressure (30MPa~60MPa): The low pressure stage is conducive to surface diffusion and pore discharge, while the high pressure stage provides sufficient sintering driving force to promote final densification, avoiding excessive driving of grain growth behavior by high pressure throughout the process.
[0089] In some embodiments of this application, the temperature of physical vapor deposition in step S2 is 400°C to 500°C.
[0090] In this application, the temperature for physical vapor deposition is controlled at 400℃ to 500℃, which is lower than the recrystallization temperature of the Co phase in the substrate. During the coating deposition process, the substrate does not undergo significant structural changes. At the same time, this temperature is sufficient to provide migration energy for the deposited atoms on the substrate surface, which is beneficial for forming a uniform and continuous coating structure. The deposition time is adjusted according to the target coating thickness.
[0091] On the other hand, this application provides a cutting tool for milling heat-resistant alloys, comprising one or more of the aforementioned carbide inserts.
[0092] The combined use of multiple cutting tools in this application allows each tool to alternately enter and exit the cutting zone during the milling process. Each tool can undergo a brief cooling during non-cutting periods, which alleviates the heat accumulation effect during continuous single-edge cutting.
[0093] In the embodiments and comparative examples of the present invention, the average particle size of the WC powder used is 0.3 μm; the average particle size of the Co powder, VC powder, TiC powder, Y2O3 powder, and La2O3 powder used is 1 μm; and the average particle size of the carbon black used is 0.1 μm.
[0094] Example 1 The carbide cutting tool provided in this embodiment has the following raw materials in weight percentage: WC powder: 84.37%, Co powder: 11%, VC powder: 1%, TiC powder: 1%, thiourea: 2.5%, Y2O3 powder: 0.05%, and carbon black: 0.08%.
[0095] In the coating: Transition layer: Cr coating, 0.2μm thick; Functional layer: TiAlVN coating, 3μm thick.
[0096] The method for preparing the cemented carbide cutting tool provided in this embodiment includes the following steps: The raw materials for matrix preparation were subjected to a first ball milling with anhydrous ethanol as the medium. The mass ratio of material, balls and anhydrous ethanol was 1:8:2. The rotation speed was 320 r / min and the time was 36 h to obtain a first ball mill slurry. The first ball mill slurry was then vacuum dried at 70℃ for 3 h to obtain a mixed powder.
[0097] The mixed powder was heated to 630°C at a rate of 8°C / min under the protection of high-purity nitrogen at a flow rate of 150 mL / min for pre-reaction heat treatment. After holding at this temperature for 3 hours, it was naturally cooled to 25°C, crushed, and then passed through a 200-mesh sieve.
[0098] 4% by weight of polyethylene glycol (molecular weight 4000) of the total raw materials for matrix preparation was added to anhydrous ethanol and heated and stirred in a water bath at 45°C until dissolved. After cooling to 25°C, it was mixed with the pre-reaction heat-treated mixed powder and subjected to a second ball milling at 120 r / min for 1.5 h to obtain a second ball mill slurry. The second ball mill slurry was vacuum dried at 70°C for 3 h and passed through a 60-mesh sieve.
[0099] The mixed powder after the second ball milling was molded, and vibration-assisted filling was used to mold it in a cold press at a pressure of 220MPa in one direction. The pressure was held for 3 minutes, and the green body was obtained after demolding.
[0100] The molded green body was immersed in water at 40°C for 2 hours, and then sintered in two steps at a heating rate of 200°C / min under 10 Pa: the first stage was heated to 1150°C, held for 8 minutes, and subjected to a pressure of 15 MPa; the second stage was further heated to 1400°C, held for 12 minutes, and subjected to a pressure of 45 MPa. After sintering, the body was allowed to cool naturally to 25°C to obtain the matrix.
[0101] After demagnetizing, grinding and polishing, sandblasting, and ultrasonic cleaning, the substrate was subjected to physical vapor deposition at a depth of 4.0 × 10⁻⁶. -3 The material was degassed at 450℃, followed by ion etching and cleaning with high-purity argon. A Cr transition layer and a TiAlVN functional layer were sequentially deposited using cathodic arc evaporation at 450℃ for 2 hours. After deposition, the material was allowed to cool naturally to 25℃ to obtain the finished cemented carbide cutting tool.
[0102] Figure 1 This is a SEM image of the cemented carbide cutting tool substrate prepared in Example 1. The image shows uniform grain size, no abnormally large grains, low porosity, no continuous bright white film at the grain boundaries, and a dense microstructure.
[0103] Example 2 The difference between the carbide cutting tool provided in this embodiment and that in Embodiment 1 is as follows: The matrix comprises the following raw materials by weight percentage: WC powder: 84.9%, Co powder: 11%, VC powder: 1%, TiC powder: 1%, thiourea: 2%, Y2O3 powder: 0.02%, and carbon black: 0.08%.
[0104] In the coating: Transition layer: Cr coating, 0.2μm thick; Functional layer: TiAlVN coating, 3μm thick.
[0105] The preparation method was carried out in accordance with Example 1.
[0106] Example 3 The difference between the carbide cutting tool provided in this embodiment and that in Embodiment 1 is as follows: The matrix comprises the following raw materials by weight percentage: WC powder: 82.84%, Co powder: 11%, VC powder: 1%, TiC powder: 1%, thiourea: 4%, Y2O3 powder: 0.08%, and carbon black: 0.08%.
[0107] In the coating: Transition layer: Cr coating, 0.2μm thick; Functional layer: TiAlVN coating, 3μm thick.
[0108] The preparation method was carried out in accordance with Example 1.
[0109] Example 4 The difference between the carbide cutting tool provided in this embodiment and that in Embodiment 1 is as follows: The matrix comprises the following raw materials by weight percentage: WC powder: 84.37%, Co powder: 11%, VC powder: 1%, TiC powder: 1%, thiourea: 2.5%, La2O3 powder: 0.05%, and carbon black: 0.08%.
[0110] In the coating: Transition layer: Cr coating, 0.2μm thick; Functional layer: TiAlVN coating, 3μm thick.
[0111] The preparation method was carried out in accordance with Example 1.
[0112] Example 5 The difference between the carbide cutting tool provided in this embodiment and that in Embodiment 1 is as follows: The matrix comprises the following raw materials by weight percentage: WC powder: 84.37%, Co powder: 11%, VC powder: 1%, TiC powder: 1%, thiourea: 2.5%, Y2O3 powder: 0.05%, and carbon black: 0.08%.
[0113] In the coating: Transition layer: Cr coating, 0.2μm thick; Functional layer: TiAlN coating, 3μm thick.
[0114] The preparation method was carried out in accordance with Example 1.
[0115] Comparative Example 1 The difference between the carbide cutting tool provided in this comparative example and Example 1 is as follows: The matrix comprises the following raw materials by weight percentage: WC powder: 84.42%, Co powder: 11%, VC powder: 1%, TiC powder: 1%, thiourea: 2.5%, and carbon black: 0.08%. (No rare earth oxides) In the coating: Transition layer: Cr coating, 0.2μm thick; Functional layer: TiAlVN coating, 3μm thick.
[0116] The preparation method was carried out in accordance with Example 1.
[0117] Comparative Example 2 The difference between the carbide cutting tool provided in this comparative example and Example 1 is as follows: The matrix comprises the following raw materials by weight percentage: WC powder: 86.87%, Co powder: 11%, VC powder: 1%, TiC powder: 1%, Y₂O₃ powder: 0.05%, and carbon black: 0.08%. (Thiourea-free) In the coating: Transition layer: Cr coating, 0.2μm thick; Functional layer: TiAlVN coating, 3μm thick.
[0118] The preparation method was carried out in accordance with Example 1.
[0119] The following performance tests were performed on the carbide cutting tools prepared in Examples 1-5 and Comparative Examples 1-2: (1) Average friction coefficient: The ball-disc method was used to test the Al2O3 ball (6mm in diameter) of the grinding workpiece, with a load of 10N, a sliding speed of 0.1m / s, a sliding distance of 500m, and a test temperature of 600℃ to test the average friction coefficient.
[0120] (2) Vickers hardness: The high temperature Vickers hardness HV5 was tested according to T-CSTM 00650-2021 "Metallic Materials High Temperature Vickers Hardness Test Method", with a test temperature of 800℃, a test force of 5kg, a holding time of 15s, and a vacuum atmosphere.
[0121] (3) Impact toughness: The impact toughness at room temperature (25℃) was tested in accordance with GB / T 1817-2017 "Test Method for Impact Toughness of Hard Alloy at Room Temperature".
[0122] (4) Transverse fracture strength: The bending strength was tested according to GB / T 3851-2015 "Method for Determination of Transverse Fracture Strength of Hard Alloy". The three-point bending method was adopted, the sample size was 5mm×5mm×35mm, the span was 30mm, and the loading rate was 1mm / min.
[0123] (5) Milling test of heat-resistant alloy: The material being machined is nickel-based high-temperature alloy GH4033. The machining method is milling, the cutting speed is 50 m / min, the depth of cut is 2 mm, the feed per tooth is 0.12 mm / z, and the cooling method is oil cooling. The failure criterion is that the wear on the tool flank reaches 0.3 mm, and the effective cutting time is recorded.
[0124] The evaluation results of various properties of the cemented carbide cutting tools prepared in Examples 1-5 and Comparative Examples 1-2 are shown in Table 1.
[0125] Table 1. Performance test results of the carbide cutting tools prepared in Examples 1-5 and Comparative Examples 1-2
[0126] According to Table 1, the carbide inserts provided in this application have an average coefficient of friction ranging from 0.26 to 0.35 at 600°C, a Vickers hardness ranging from 955 HV5 to 1030 HV5 at 800°C, and an impact toughness ranging from 5.3 J / cm² at 25°C. 2 ~6.7J / cm 2 The bending strength ranges from 3580MPa to 3820MPa, and the effective cutting time for milling nickel-based superalloy GH4033 ranges from 39min to 47min.
[0127] Compared to Example 1, Comparative Example 1 did not include Y₂O₃ in its matrix formulation. Thiourea decomposes during the pre-reaction heat treatment to produce active nitrogen and sulfur atoms. The active nitrogen atoms can participate in the formation of carbonitride solid solutions; therefore, although the high-temperature hardness is lower than that of Example 1, it is higher than that of Comparative Example 2. This may be because the active sulfur atoms, lacking Y₂O₃, react with it to form stable rare-earth sulfur oxides, easily causing "sulfur embrittlement," resulting in a 93% increase in the average coefficient of friction compared to Example 1, a 49% decrease in impact toughness, and an 18% decrease in flexural strength. Furthermore, the absence of Y₂O₃ may lead to the disappearance of the grain boundary pinning effect, causing WC grains to grow abnormally locally during high-temperature sintering, resulting in a 38% reduction in effective cutting time compared to Example 1.
[0128] Compared to Example 1, Comparative Example 2 did not contain thiourea in its matrix formulation. Without thiourea, no active nitrogen or sulfur atoms were generated during the pre-reaction heat treatment. This may be because the absence of active nitrogen atoms prevented the formation of carbonitride solid solutions, resulting in a 24% decrease in high-temperature hardness compared to Example 1. The absence of active sulfur atoms also prevented the formation of rare earth sulfur oxides; only trace amounts of sulfur impurities in the raw materials were partially fixed by Y₂O₃, leading to a 78% increase in the average coefficient of friction compared to Example 1. Although the impact toughness and flexural strength decreased by 39% and 10% respectively compared to Example 1, they were still superior to Comparative Example 1. The effective cutting time was shortened by 43% compared to Example 1.
[0129] The carbide inserts provided by this invention exhibit excellent fracture resistance in the milling of heat-resistant alloys, and maintain high hardness and wear resistance without significant softening even under high-temperature heating conditions. They are suitable for efficient milling of aerospace heat-resistant alloy components.
[0130] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A cemented carbide cutting tool, characterized in that, The coating comprises a substrate and a coating disposed on the substrate, wherein the substrate comprises the following raw materials in weight percentages: WC: 81.5%–86.5%, Co: 10%–12%, VC: 0.75%–1.5%, TiC: 0.75%–1.5%, thiourea: 2%–4%, rare earth oxides: 0.02%–0.08%, and carbon black: 0.05%–0.15%; The rare earth oxide is Y2O3 or La2O3.
2. The cemented carbide cutting tool according to claim 1, characterized in that, The coating comprises a transition layer and a functional layer sequentially disposed on the substrate.
3. The cemented carbide cutting tool according to claim 2, characterized in that, The transition layer in the coating is Cr; And / or, the thickness of the transition layer in the coating is 0.1 μm to 0.3 μm; And / or, the functional layer in the coating is at least one of TiAlN coating, AlTiN coating, TiSiN coating, TiAlVN coating, and TiAlSiN coating; And / or, the thickness of the functional layer in the coating is 2μm to 5μm.
4. The method for preparing cemented carbide cutting tools according to any one of claims 1-3, characterized in that, Includes the following steps: S1: After mixing the raw materials for preparing the matrix, the mixture is subjected to a first ball milling and a pre-reaction heat treatment under a protective atmosphere to obtain a mixed powder; a water-soluble binder is added to the mixed powder and the mixture is subjected to a second ball milling, and then molded into a green body; the green body is then subjected to spark plasma sintering to obtain the matrix. S2: A coating is prepared on the substrate obtained in step S1 using physical vapor deposition.
5. The method for preparing cemented carbide cutting tools according to claim 4, characterized in that, The rotational speed of the first ball mill in step S1 is 300 r / min to 350 r / min; And / or, the first ball milling time in step S1 is 24h to 48h; And / or, the rotational speed of the second ball mill in step S1 is 80 r / min to 150 r / min; And / or, the second ball milling time in step S1 is 1h to 2h.
6. The method for preparing cemented carbide cutting tools according to claim 4, characterized in that, The flow rate of the protective atmosphere in the pre-reaction heat treatment in step S1 is 100 ml / min to 200 ml / min; And / or, the heating rate of the pre-reaction heat treatment in step S1 is 5℃ / min to 10℃ / min; And / or, the temperature of the pre-reaction heat treatment in step S1 is 550℃~700℃; And / or, the heat treatment holding time in step S1 is 2h to 4h.
7. The method for preparing cemented carbide cutting tools according to claim 4, characterized in that, The compression molding pressure in step S1 is 200MPa to 250MPa; And / or, the vacuum degree of the discharge plasma sintering in step S1 is 5 Pa to 15 Pa; And / or, the heating rate of the discharge plasma sintering in step S1 is 150℃ / min to 250℃ / min; And / or, in step S1, the discharge plasma sintering is divided into a first-stage sintering and a second-stage sintering.
8. The method for preparing cemented carbide cutting tools according to claim 7, characterized in that, The sintering temperature in the first stage of step S1 is 1100℃~1200℃; And / or, the holding time for the first stage sintering in step S1 is 5 min to 10 min; And / or, the sintering pressure in the first stage of step S1 is 10MPa to 20MPa; And / or, the sintering temperature in the second stage of step S1 is 1340℃~1450℃; And / or, the holding time for the second stage sintering in step S1 is 5 min to 15 min; And / or, the pressure of the second stage sintering in step S1 is 30MPa to 60MPa.
9. The method for preparing a cemented carbide cutting tool according to claim 4, characterized in that, The temperature for physical vapor deposition in step S2 is 400℃~500℃.
10. A cutting tool for milling heat-resistant alloys, comprising one or more carbide inserts according to any one of claims 1-3.